Bypassing mitochondrial defects rescues Huntington's phenotypes in Drosophila - Campesan, Susanna; del Popolo, Ivana; Marcou, Kyriaki; Straatman-Iwanowska, Anna; Repici, Mariaelena; Boytcheva, Kalina V.; Cotton, Victoria E.; Allcock, Natalie; Rosato, Ezio; Kyriacou, Charalambos P.; Giorgini, Flaviano (Neurobiology of disease, 2023)
Huntington's disease (HD) is a fatal neurodegenerative disease with limited treatment options. Human and animal studies have suggested that metabolic and mitochondrial dysfunctions contribute to HD pathogenesis. Here, we use high-resolution respirometry to uncover defective mitochondrial oxidative phosphorylation and electron transfer capacity when a mutant huntingtin fragment is targeted to neurons or muscles in Drosophila and find that enhancing mitochondrial function can ameliorate these defects. In particular, we find that co-expression of parkin, an E3 ubiquitin ligase critical for mitochondrial dynamics and homeostasis, produces significant enhancement of mitochondrial respiration when expressed either in neurons or muscles, resulting in significant rescue of neurodegeneration, viability and longevity in HD model flies. Targeting mutant HTT to muscles results in larger mitochondria and higher mitochondrial mass, while co-expression of parkin increases mitochondrial fission and decreases mass. Furthermore, directly addressing HD-mediated defects in the fly's mitochondrial electron transport system, by rerouting electrons to either bypass mitochondrial complex I or complexes III-IV, significantly increases mitochondrial respiration and results in a striking rescue of all phenotypes arising from neuronal mutant huntingtin expression. These observations suggest that bypassing impaired mitochondrial respiratory complexes in HD may have therapeutic potential for the treatment of this devastating disorder. •Huntington's disease model fruit flies exhibit mitochondrial dysfunction.•The E3 ubiquitin ligase parkin ameliorates these defects in fly neurons and muscles.•Parkin ameliorates shortened lifespan and neurodegeneration in these flies.•Bypassing electron flow to mitochondrial complexes I or III-IV is neuroprotective.•Modulating mitochondrial function is a possible route for therapy.